Everyday datafication and higher education: Student agency, trust and resignation - Noteboom, Joe (Proceedings of the International Conference on Networked Learning, 2024)
Datafication—the transformation of human life into quantifiable digital data—raises important questions for student agency in higher education. Student agency is central to learning and engagement within university, and the development of agentic selves in students forms a core purpose of higher education. Data-driven practices such as learning analytics promise to support the development of student agency in the context of learning, while at the same time introducing new information and power asymmetries into the relationship between students and the university. Critical research on datafication, meanwhile, has highlighted the threats to student agency posed by data-driven analytics practices that reinforce structural inequalities and depend on the surveillance of student behaviours and bodies. This paper explores student agency in relation to datafication through a discussion of the findings of ethnographic research with university students in Scotland. Drawing on literature from the field of critical data studies that focuses on people’s everyday experiences of datafication, the paper will highlight how students understand, feel about and respond to datafication in their everyday lives, and what this means for their relationship with the university. Students draw on a range of everyday data literacies developed through their experiences of datafied platforms and academic knowledge to make sense of university data practices. They employ diverse tactics for coping with datafication, including minimizing perceived risks by taking measures to protect their privacy and disconnecting from certain platforms. They tend to trust the university with their data, but this trust is conditional and closely related to their overall perception of the university. Above all, perhaps, students are resigned to datafication within and beyond the university. Thus, while students demonstrate agency with respect to datafication in a range of ways, data relations between the university and students are fundamentally top-down, reflecting wider societal dynamics whereby people routinely give up their data in exchange for access to digital services, with little ability to opt out or control what happens to it. Universities, it will be argued, have the potential to introduce participatory forms of data governance that reframe these relations, thus supporting the development of student agency over datafication within and beyond the university.